Developing intercultural communicative competence in foreign language educationat a private university (Shimmering Words: Research and Pedagogy E-Journal, 2020)
This reflective article analyzes a pedagogical experience carried out at a private university in the city of Tunja, Colombia. I was worked with mechanical engineering and civil engineering majors enrolled in a second and fourth semester English course, respectively. The study aimed at developing the intercultural communicative competence through communicative activities with North American assistant professors or co-teachers. Data was collected through interviews, video recording, and journals. The findings revealed that activities based on interaction and language strategies can help students develop their intercultural communicative competence (ICC). The study also showed that personality traits were a factor that influenced the development of ICC.
Keywords: Language; culture; foreign language education; intercultural communicative competence; interaction